Air pollution modifies colonisation factors in beneficial symbiont Snodgrassella and disrupts the bumblebee gut microbiome - Hannah R. Sampson; Natalie Allcock; Eamonn B. Mallon; Julian M. Ketley; Julie A. Morrissey (npj Biofilms and Microbiomes)
Abstract Particulate air pollutants, a major air pollution component, are detrimental to human health and a significant risk to wildlife and ecosystems globally. Here we report the effects of particulate pollutant black carbon on the beneficial gut microbiome of important global insect pollinator, the buff-tailed bumblebee (Bombus terrestris). Our data shows that exposure to black carbon particulates alters biofilm structure, gene expression and initial adhesion of beneficial bee gut coloniser, Snodgrassella alvi. Exposure of adult Bombus terrestris to non-toxic black carbon particulates significantly increased viable bacteria on MRS agar and 16S absolute abundance of beneficial bacteria Bombilactobacillus in Post-treated bumblebees compared to Pre-treated, demonstrating disruption of the bumblebee gut microbiome. These findings show that black carbon exposure has direct, measurable effects on bees’ beneficial commensal bacteria and microbiome. Together these data highlight that black carbon, a single type of particulate pollution, is an underexplored risk to insect pollinator health.